Safety of higher dosages of Viscum album L. in animals and humans - systematic review of immune changes and safety parameters - Kiene Helmut; Grugel Renate; Kienle Gunver S (BMC, 2011)
Abstract Background Viscum album L extracts (VAE, mistletoe) and isolated mistletoe lectins (ML) have immunostimulating properties and a strong dose-dependent cytotoxic activity. They are frequently used in complementary cancer treatment, mainly to improve quality of life, but partly also to influence tumour growth, especially by injecting VAE locally and in high dosage. The question is raised whether these higher dosages can induce any harm or immunosuppressive effects. Methods Systematic review of all experiments and clinical studies investigating higher dosages of VAE in animals and humans (Viscum album > 1 mg in humans corresponding to > 0.02 mg/kg in animals or ML > 1 ng/kg) and assessing immune parameters or infections or adverse drug reactions. Results 69 clinical studies and 48 animal experiments reported application of higher doses of VAE or ML and had assessed immune changes and/or harm. In these studies, Viscum album was applied in dosages up to 1500 mg in humans and 1400 mg/kg in animals, ML was applied up to 6.4 μg/kg in humans and in animals up to 14 μg/kg subcutaneously, 50 μg/kg nasally and 500 μg/kg orally. A variety of immune parameters showed fluctuating or rising outcomes, but no immunosuppressive effect. Side effects consisted mainly of dose-dependent flu-like symptoms (FLS), fever, local reactions at the injection site and various mild unspecific effects. Occasionally, allergic reactions were reported. After application of high doses of recombinant ML, reversible hepatotoxicity was observed in some cases. Conclusions Application of higher dosages of VAE or ML is not accompanied by immunosuppression; altogether VAE seems to exhibit low risk but should be monitored by clinicians when applied in high dosages.